The identity of Aster lushiensis (Asteraceae) - Fu, Zhixi; Zhang, Caifei; Gao, Tiangang (Phytotaxa, 2013)
Aster lushiensis (J.Q.Fu 1983: 110) Brouillet, Semple & Y.L.Chen (2011: 607) (Astereae, Asteraceae) was recently combined from the genus Gymnaster Kitamura (1937: 301) (=Miyamayomena Kitamura (1982: 409)) without a study of specimens. It is only known from the type specimens collected in Lushi County, Henan Province, China. Examination of morphological characters of types showed that it is conspecific with Chrysanthemum vestitum (Hemsley 1888: 438) Stapf (1933: t. 9330) (Anthemideae; Shih et al. 2011), and is here reduced to a synonym of the latter species.